Supplementation of Alhagi honey polysaccharides contributes to the improvement of the intestinal immunity regulating the structure of intestinal flora in mice. Issue 20 (25th August 2021) - Cai, Gaofeng; Wusiman, Adelijiang; Gu, Pengfei; Mao, Ningning; Xu, Shuwen; Zhu, Tianyu; He, Jin; Liu, Zhenguang; Wang, Deyun
Abstract : Supplementation of Alhagi honey polysaccharides contributes to the improvement of the intestinal immunity and regulating the structure of intestinal flora in mice. Abstract : Alhagi honey polysaccharides (AH), a main active component of Alhagi honey, are known to possess excellent pharmacological activities and have been widely used as dietary supplements in traditional Chinese medicine for thousands of years. This study is aimed to investigate the heath effect of AH on murine intestinal mucosal immune function and composition of the gut microbiome. ICR mice received daily intragastric administration of AH (three dosages, 200 mg kg −1, 400 mg kg −1, and 800 mg kg −1 ) or saline for 7 consecutive days. Results indicated an improvement in the intestinal barrier function through increases in secretory immunoglobulin A (sIgA) and β-defensins. Simultaneously, AH also significantly stimulated IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ, and TNF-α cytokine secretion as compared to the control samples. Moreover, hematoxylin and eosin staining showed that AH enhanced the number of intraepithelial lymphocytes (IELs) in the small intestine. An obvious increase in the ratio of IgA + cells of AH-treatment samples in the lamina propria was also detected by immunohistochemical staining. In addition, the CD3 +, CD4 + and CD8 + T-cell ratio in mesenteric lymph nodes and Peyer's patches in the AH-treatment was significantly higher than that in the control group. Furthermore, 16S rDNA gene sequencing was used to monitor the dynamic changes in the gut microbiota. The result revealed that AH significantly increased the indexes of Shannon and obviously decreased the indexes of Simpson, suggesting the enhancement of the diversity and richness of the intestinal microbiome. Moreover, AH modulated the gut microbiome via increasing the abundance of probiotics and decreasing the levels of pathogenic bacteria. In summary, these results indicated that AH could be used as a prebiotic to enhance murine intestinal mucosal immunity and to modulate the gut microbiome.